EKSTRAKSI JAMUR AURICULARIA DENGAN MENGGUNAKAN PELARUT ETANOL DAN METANOL - Yuliarni, Floreta Fiska; Ayu Puji Lestari, Kinanti; Kun Arisawati, Diah; Dwi Winda Sari, Ratna; Ratna K., Kharisma (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2022)
The purpose of this study was to determine the characteristics of Auricularia extract which was extracted using 96% ethanol (sample E) and methanol (sample M). Auricularia was powdered before extraction. Extraction of mushrooms was carried out using the maceration method for three days. The solvents used for extraction were 96% ethanol and methanol. The extract that has been obtained is calculated by weight yield, tested for solubility, pH, and organoleptic tests. The yield weight of sample E was 1.47% higher than sample M, which was 1.22%. In the solubility test, sample E dissolved in water had a higher solubility of 60% compared to 96% ethanol, which was 55%, on the other hand, sample M dissolved in ethanol 96% had a higher solubility of 55% compared to 40% in water. Samples E and M dissolved in water had the same pH of 5, as well as those dissolved in 96% ethanol, which was 6. The organoleptic test on samples E and M had similarities in smell and shape, the difference was the color. The conclusion is samples E and M have almost the same characteristics.